Performance analysis of 3D assets in virtual reality simulations for climate change: a case study in sustainable energy systems - Miranto, Cahya; Firmanda, Ardiman; Rante, Hestiasari; Sukaridhoto, Sritrusta; Agus Zainuddin, Muhammad; Rahman, Haolia (Institute of Advanced Engineering and Science, 2025)
This study investigates the performance impact of 3D assets in a virtual reality (VR) simulation designed for climate change education, aiming to balance visual fidelity and system efficiency on standalone headsets. Using a case study modeled on a sustainable energy environment, key performance metrics frames per second (FPS), triangle count, and draw calls were measured to assess the effect of object density, material transparency, and batching strategies. Experimental results show that configurations with 20 trees and 20 characters maintained 101 FPS, while denser scenes with 30 trees and 30 characters dropped to 79 FPS approaching the minimum usability threshold for VR. Transparent tree foliage with alpha-cutout materials imposed higher graphics processing unit (GPU) loads than high-triangle opaque character models, highlighting the performance cost of material complexity. These findings offer practical guidelines for optimizing asset configurations in immersive educational VR content. Future work may explore integration of artificial intelligence (AI) behavior and user interaction to assess broader system performance.